On the Light Curves of Disk and Bulge Novae - Asaf Cohen; Dafne Guetta; Yael Hillman; Massimo Della Valle; Luca Izzo; Volker Perdelwitz; Mario Livio (The Astrophysical Journal)
We examine the light curves of a sample of novae, classifying them into single-peaked and multiple-peaked morphologies. Using accurate distances from Gaia, we determine the spatial distribution of these novae by computing their heights, Z , above the Galactic plane. We show that novae exhibiting a single peak in their light curves tend to concentrate near the Galactic plane, while those displaying multiple peaks are more homogeneously distributed, reaching heights up to 1000 pc above the plane. A K-S test rejects the null hypothesis that the two distributions originate from the same population at a significance level corresponding to 4.2 σ .